If a^2 + b^2 = 5ab, then the value of (a^2/b^2 + b^2/a^2) is : (a) 32 (b) 16 (c) 23 (d) -23
To find the ratio of two numbers given that the square of their sum is equal to four times their product, let's denote the two numbers as \(a\) and \(b\). According to the given condition, we have: \[ (a + b)^2 = 4ab \] Expanding the left side of the equation gives: \[ a^2 + 2ab + b^2 = 4ab \] RearrRead more
To find the ratio of two numbers given that the square of their sum is equal to four times their product, let’s denote the two numbers as \(a\) and \(b\). According to the given condition, we have:
\[
(a + b)^2 = 4ab
\]
Expanding the left side of the equation gives:
\[
a^2 + 2ab + b^2 = 4ab
\]
Rearranging the terms to bring them all to one side:
\[
a^2 + 2ab – 4ab + b^2 = 0
\]
Simplifying:
\[
a^2 – 2ab + b^2 = 0
\]
Notice that the left side of the equation now represents the square of the difference between \(a\) and \(b\):
\[
(a – b)^2 = 0
\]
For a square to equal zero, the quantity being squared must itself be zero:
\[
a – b = 0
\]
This implies:
\[
a = b
\]
Therefore, the ratio of \(a\) to \(b\) is \(1:1\), which means the correct answer is:
(c) \(1: 1\)
See less
Calculation of the Given Expression Given the equation \(a^{2}+b^{2}=5ab\), we are tasked with determining the value of the expression \(\left(\frac{a^{2}}{b^{2}}+\frac{b^{2}}{a^{2}}\right)\). Step 1: Simplify the Given Relation Starting with the given equation, we divide both sides by \(ab\) to simRead more
Calculation of the Given Expression
Given the equation \(a^{2}+b^{2}=5ab\), we are tasked with determining the value of the expression \(\left(\frac{a^{2}}{b^{2}}+\frac{b^{2}}{a^{2}}\right)\).
Step 1: Simplify the Given Relation
Starting with the given equation, we divide both sides by \(ab\) to simplify:
\[
\frac{a^2 + b^2}{ab} = 5
\]
This leads to:
\[
\frac{a}{b} + \frac{b}{a} = 5
\]
Step 2: Square Both Sides
To find the value of \(\left(\frac{a^{2}}{b^{2}}+\frac{b^{2}}{a^{2}}\right)\), we square both sides of the simplified equation:
\[
\left(\frac{a}{b} + \frac{b}{a}\right)^2 = 5^2
\]
This yields:
\[
\frac{a^2}{b^2} + 2\left(\frac{a}{b}\cdot\frac{b}{a}\right) + \frac{b^2}{a^2} = 25
\]
Given that \(\frac{a}{b}\cdot\frac{b}{a} = 1\), we simplify further:
\[
\frac{a^2}{b^2} + \frac{b^2}{a^2} + 2 = 25
\]
Step 3: Isolate the Target Expression
Subtracting 2 from both sides to isolate the expression gives us:
\[
\frac{a^2}{b^2} + \frac{b^2}{a^2} = 25 – 2 = 23
\]
Conclusion
Therefore, the value of the expression \(\left(\frac{a^{2}}{b^{2}}+\frac{b^{2}}{a^{2}}\right)\) is \(\textbf{23}\), making the correct answer:
(c) \(\textbf{23}\)
This solution methodically derives the value of the given expression by leveraging the initial condition and algebraic manipulation, leading to a clear and logical conclusion.
See less